2003
DOI: 10.2223/jped.1025
|View full text |Cite
|
Sign up to set email alerts
|

Use of asthma controller drugs at admission to a pediatric pulmonology outpatient clinic

Abstract: Objective: inhaled corticosteroids are widely used in developed countries. On the other hand, due to its high cost, this kind of drug is underused in asthmatic patients living in developing countries. The present study aims at verifying the use of controller medication in children with moderate or severe persistent asthma at admission to a specialized outpatient facility.Methods: descriptive study with 560 children aged 4 to 14, with diagnosed asthma, who were admitted between April 1996 and December 2000. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Inhaled corticosteroids, the main pharmacological choice for control of this disease, were reported to have been used by only one child in this population. Other studies conducted in Brazil, although focused on children cared for in health units, found frequencies of use of inhaled corticosteroids between 2 and 6% [ 18 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhaled corticosteroids, the main pharmacological choice for control of this disease, were reported to have been used by only one child in this population. Other studies conducted in Brazil, although focused on children cared for in health units, found frequencies of use of inhaled corticosteroids between 2 and 6% [ 18 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rosário Filho reported an increase in spending on drugs for asthma treatment and in hospitalizations due to this disease [ 16 ]. Other studies performed in children with asthma in the public health care facilities in Brazil revealed small proportions of use of anti-inflammatory treatment, ranging from 6.0 to 14.0% [ 17 , 18 ]. In Brazil, the lack of population-based studies on the use of anti-asthmatics in children, as well as on the reasons for this lack, necessitates such studies, particularly as the use of these drugs is considered an indirect indicator of quality of care provided to asthmatic children.…”
Section: Introductionmentioning
confidence: 99%